Making sense of China's Economic Slowdown - Yasushi Suzuki (Journal of Economics and Political Economy, 2014)
This paper aims to review the factors inducing China's successful economic transformation, so as to find the causes of the subsequent economic slowdown, from the New Institutional Economics (NIE) viewpoint and the Marxian viewpoint, respectively. The former school is primarily concerned about the "supply-side" driver (changing rules of game for producers) of increasing economic output and efficiency, while the latter is basically sharing with the Marxian concern of the "demand-side" driver (an egalitarian pattern of income distribution which underpins mass-consumption) of increasing economic output and sustainability. NIE emphasize that unless a free and open market for ideas is created, China cannot sustain its economic growth or advance itself into a global centre of technological innovation or scientific discovery. However, this paper points out that the creation of an active market for ideas would not always guarantee the sustainability of economic growth, drawing the lessons from Japan's experiences. This paper suggests that it takes more or less several years to create an active market for ideas to transform to a new phase of post-industrialization. In addition, in the phase of post-industrialization, rapid product obsolescence is brought by severe competition in which rival firms are accelerating the introduction of competitive products to the market, which may expose innovative firms to fundamental uncertainty.
Keywords: B51; P30; P20; 330; Economic transformation; Market socialism; Post-industrialization; China